Two new species of deep-water xanthid crabs of the genera Euryxanthops Garth & Kim, 1983, and Medaeops Guinot, 1967 (Crustacea: Decapoda: Brachyura: Xanthidae) from New Zealand - Ng, Peter K.l.; Mclay, Colin L. (Zootaxa, 2007)
Two new species of deep-water xanthid crabs, Euryxanthops chiltoni, new species, and Medaeops serenei, new species, are described from the Kermadec Islands, New Zealand. This is the first time these genera are reported from New Zealand. Keys for the identification of all species of Euryxanthops and Medaeops are provided. The two new species bring the total number of species of xanthids from the Kermadec Is. to 17, and the known species of Euryxanthops and Medaeops to five and six respectively;. Although caught in the vicinity of hydrothermal vents, there is no evidence that these species are directly dependent upon the vent community.